10. IMPORTANCE OF RAILWAY TRANSPORT IN REGIONAL DEVELOPMENT - Salimov Bakhriddin Lutfullaevich. Ismoilov Asilbek Ulug’bekovich (Innovative technologies in construction Scientific Journal, 2023)
The article provides information about the emergence of railway transport and its introduction into Central Asia. Also, it was analyzed that during the years of independence, unprecedented works were carried out in the field of development of railway transport, economy and technology, as a result of efficient management of resources, along with all types of transport in Uzbekistan